Fatwa Method of the Muhammadiyah Tarjih Council (Analysis of Al Maqashid Syariah Against Fatwa No. 26.B of 2003 and Fatwa No. 25 of 2004) - Abdullah, Aris (Riviera Publishing, 2025)
This research examines the methodology employed by Muhammadiyah's Tarjih Council in issuing fatwas on food-related cases, particularly concerning tape (fermented food containing alcohol), and analyzes these rulings through Jasser Auda's contemporary maqasid al-shariah perspective. Using a qualitative descriptive design, the study draws from textual sources including academic journals, books, and the Indonesian Ulema Council's Fatwa No. 26.B of 2003 and No. 25 of 2004. The findings reveal that while alcohol is fundamentally prohibited (haram) due to its harm to the human body, the Tarjih Council's fatwa on tape consumption remains ambiguous, permitting alcohol content below 5% without clear justification. Auda's maqasid framework highlights the need to balance religious principles with modern contexts, emphasizing the protection of religion (din), intellect ('aql), life (nafs), and lineage (nasl). This research underscores the importance of contextualizing Islamic legal rulings to address contemporary challenges. It calls for clearer fatwa formulations that integrate scientific evidence and maqasid-based reasoning, ensuring both religious compliance and public health safeguards. The findings contribute to ongoing discourse on Islamic jurisprudence reform and offer practical guidance for halal certification bodies in regulating fermented products.